Margaret Bent, The Motet in the Late Middle Ages (New York, Oxford University Press, 2023), 776 pp., ISBN: 9780190063771 - Stoessel, Jason (Revista Portuguesa de Musicologia, 2025)
Recensão: Margaret Bent, The Motet in the Late Middle Ages (New York, Oxford University Press, 2023), 776 pp., ISBN: 9780190063771